An Analysis Of The ESP Textbook 'English For Specific Purposes For Meetings' Based Tomlinson's Theory - Abdul Syahid; Ahmad Julianto; Alvin Maulana; Muhammad Rafi Zidan; Muhammad Hidayatur Rahman (Universitas Maritim AMNI Semarang, 2024)
This study evaluates the effectiveness of the